Manager Skills in Virtual-Network Conditions : an Attempt at Identification in the Light of Survey Research - Kołodziejczyk, Agnieszka; Antczak, Zbigniew (Umiejętności menedżera w warunkach wirtualno-sieciowych : próba identyfikacji w świetle badań ankietowych, 2010)
Co-ordinating, motivating and building flexible teams, by using modern telecommunication solutions, are the elements of managing the virtual-network structure. Manger responsible for managing in virtual-network structure plays a co-ordinating role, making efforts to fully take advantage of skills and knowledge of the team members by inspiring and creating issues to solve in the scope of tasks realized by the team. Skills required for virtual manager who leads the virtual-network team are: ability to build the virtual, network team and co-ordinate it from distance, awareness of network, inter-organizational, virtual, international strategy, efficiency in communicating (individual emotional intelligence) by using modern IC techniques as well as building and maintaining organizational culture.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 108-118
Keywords: virtual manager; virtual-network manager; virtual-network team; virtual organization; manager's skills; emotional intelligence